Preventive maintenance development: a case study in a furniture company - Carvalho, Bruno António Gonçalves de (2015)
This article intends to present a project in a furniture manufacturing factory, carried out to improve the efficiency of preventive maintenance actions, decreasing the number of failures and downtime of equipment, and maintenance costs. An initial diagnosis allow identifying the main weaknesses of the maintenance department, especially concerning preventive maintenance, one the pillars of TPM methodology and on which the factory is based for maintaining their equipment. There was a small percentage of planned preventive interventions actually performed and an unbalanced allocation of tasks by the available resources. In order to improve the efficiency of maintenance staff, standard preventive maintenance instructions was developed. An approach to the planning and allocation of tasks throughout the year by service technicians was also defined. There was a positive impact of the improvement actions and the new way of tasks allocation led to a better balance of the tasks among service technicians, as well as an increase in the number of performed preventive interventions.